Core-matched nanoassemblies for targeted co-delivery of chemotherapy and photosensitizer to treat drug-resistant cancer. (1st April 2019) - Jiang, Di; Xu, Minjun; Pei, Yuanyuan; Huang, Yukun; Chen, Yu; Ma, Fenfen; Lu, Huiping; Chen, Jun
Graphical abstract: Abstract: Emergence of drug resistance in tumors causes therapeutic failure or tumor relapse. Combination of chemotherapy and photodynamic therapy holds significant promise to treat drug-resistant tumors. However, stubborn hydrophobicity of photosensitizer (PS), low encapsulation efficiency and leaking problem of PS in organic carrier, and disparate physicochemical properties of PS and chemotherapeutics make the combination unachievable. Thus how to efficiently co-deliver the two functional agents to enable photo-chemotherapy seems to be one of the key challenges. Here, core-matched technology (CMT) was developed to realize efficient co-delivery of PS and chemotherapeutics, in which PS verteporfin (VP), tumor angiogenesis-targeting iNGR peptide and poly(lactic acid) (PLA) were respectively pre-modified with D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS), and the conjugates self-assembled into iNGR-modified and VP conjugated nanoassemblies (iNGR-VP-NA) with chemotherapeutic agent docetaxel (DTX) loaded in the hydrophobic core. The obtained iNGR-VP-NA-DTX was characterized by mean size of 166.0 ± 9.2 nm and morphology of uniformly spherical shape. In vitro, with the assistance of laser, iNGR-VP-NA-DTX exhibited higher cellular uptake, stronger cytotoxicity in HUVEC cells, drug-resistant HCT-15 tumor cells and more effective inhibition of tube formation than iNGR-VP-NA-DTX without laser or VP-NA-DTX with laser. After intravenously injected into mice, through the near-infrared light emitted by VP, iNGR-VP-NA exhibited improved accumulation compared to VP-NA in drug-resistant HCT-15 tumor. Besides, iNGR-VP-NA-DTX with laser enhanced inhibition of angiogenesis and induced severe apoptosis and necrosis in tumor tissues along with minimal impact to normal areas. These evidences demonstrated that iNGR-VP-NA-DTX was of great potential to treat drug-resistant tumors via efficient angiogenesis-targeted photo-chemotherapy. Statement of Significance: Combination of chemotherapy and photodynamic therapy is thought to be a potential approach to treat drug-resistant cancer. However, it is difficult to realize optimized photo-chemotherapy in one nano-system. Here, iNGR-modified nanoassemblies is created based on core-matched nanotechnology to realize targeted photo-chemotherapy. In this study, the improved co-loading of chemotherapy and photosensitizer in the nanoassemblies exerted a synergistic anti-tumor effect and the decoration with iNGR enhanced tumor-targeting efficiency. In the presence of laser irradiation, the nanoassemblies exhibited enhanced and targeted anti-tumor efficacy in drug-resistant HCT-15 tumor both in vitro and in vivo .